Approaches to indigenous theatre in the contemporary scene (The Voz a Vos Bulletin, 2024)
The question of whether or not pre-Columbian theatre existed is very important for the current state of Colombian theatre and society. Although there was no theatre in our territories similar to the western one we know, born from the Dionysian festivals or their Roman or medieval forms, we must recognize that thanks to the studies of Fernando González Cajiao, Rosario Jaramillo, Carlos José Reyes, and Marina Lemus, Liliana Alzate, Carlos Araque, Zapata Olivella, Floresmiro Masabel, among others, together with the multiple chronicles of Indians, archaeological, anthropological, linguistic and cultural discoveries as well as the relationship with Indigenous communities and their orality, that there did exist in pre-Columbian times multiple Indigenous communities that held festivals, celebrations, sacrifices, offerings, processions and ritual acts whose elements and intentionality resemble both the origin and the development of what we know today as theatre. The similarities and parallels found between the rituals to the god Dionysus and the dances, songs, and sacrifices of the Muisca God Fu, Fo, or Nemcatacoa are evidence of this. The festive, sacred, and community character of the theatre was revived in different ways in both territories.The pre-Columbian stage performances and their proximity to ritual, magic, medicine, orality, myth, anthropomorphism, and currently with a series of political and social demands in favor of inclusion, equality, and identity make the relationship between theatre – indigenous communities – education of fundamental importance in modern theatre and our present stage.Beyond making an exhaustive study of the aforementioned authors and their works that are available for public consultation, our interest is to recognize the importance of their works by revealing some resonances for the contemporary theater scene, by disseminating part of the scenic exploration of the Inti Amaru Artistic and Cultural Foundation, asking ourselves: What could be the role of professionals in the performing arts in the face of the current situation of ethnic communities?An inquiry that since 2019 led us to contemplate the creation of the concept of Indigenist Theater and with which we began a theatrical movement with actions such as virtual conversations, training laboratories, circulation seasons, publications, and the creation of the Indigenous and Afro-Colombian Theater Festival that celebrates its fourth version this year and to which you are cordially invited in Bogotá.
Keywords: Ritual; Indigenism and education; Theatre; Dramaturgy